Manajemen Pendidikan Karakter dalam Pembentukan Profil Pelajar Pancasila di Kecamatan Bakam Kabupaten Bangka - Kusumaningrum, Ambar; Lestari, Slamet (Universitas Negeri Makassar, 2025)
This study analyzes character education management in shaping the Pancasila Student Profile (P3) at SMP Negeri 2 and 3 Bakam, Bangka Regency. Using a qualitative method, data were collected through interviews, observations, and documentation. The findings indicate that P3 management involves planning (education report analysis, annual work plans, and training), organizing (task distribution among teachers and staff), implementation (integration of P3 values into learning and extracurricular activities), and supervision (regular evaluation and reflection). The main challenges include limited facilities and internal and external factors, which are addressed through support from educators and external parties. Further studies are recommended for schools facing difficulties in implementing P3.